Electrodes Configuration Effect on Some Properties of Low Temperature Plasma Jet (LTPJ) (International Journal of Current Engineering and Technology, 2014)
In this work the development of a non-equilibrium atmospheric pressure plasma torch by use of two electrodes configuration, the linear-field configuration and cross–filed configuration. Where the experimental set up is based on very simple and low cost electric components, and generates an electrical field sufficiently high at the electrodes to ionize various gases, which flow at atmospheric pressure. The working gas (Ar) was supplied to flow through the torch with adjustable flow rate by flow meter regulator. In all cases of configuration the high voltage power supply generates high voltage of sinusoidal shape of 7.5 kV peak to peak and frequency of 28 kHz. The optical characterization was made by taking the spectrum of discharge by optical emission spectrometer. The electron temperature for the two electrodes configuration was identified spectrally, and its value is about 1.75eV. Also the effects of the gas flow rate on working gas temperature have been studied.
Keywords: Plasma torch, non-thermal plasma jet, electron temperatures measurement